ANALYSIS OF THE INFLUENCE OF MONEY SUPPLY, INTEREST RATES, AND EXCHANGE RATES ON INFLATION IN INDONESIA - Christine Adeina Sihotang; Bakhtiar Efendi; Dewi Mahrani Rangkuty (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
There are many factors that can affect inflation, both internal and external. The rate of inflation is also influenced by other factors such as increased economic activity that drives an increase in aggregate demand not matched by an increase in aggregate supply due to structural economic constraints. This research aims to determine the influence of money supply, interest rates, and exchange rates on inflation in Indonesia, both partially and simultaneously. This is a quantitative study using secondary (time series) data obtained from the Central Statistics Agency (BPS), Bank Indonesia, and the Ministry of Finance over a period of 31 years, from 1993 to 2023. The data analysis technique used is the Multiple Linear Regression Equation. The results of this study indicate that partially, money supply and interest rates have a positive and significant effect on inflation in Indonesia, while the exchange rate does not have a significant effect on inflation in Indonesia. Simultaneously, it is found that money supply, interest rates, and exchange rates together influence inflation in Indonesia.